Process-Ready Nickel-Catalyzed Suzuki-Miyaura Coupling Enabled by tri -ProPhos - Yang, Jin; Zhao, Hengyuan; Schultz, Johnathan E; Wisniewski, Steven R; Simmons, Eric M; Diao, Tianning (ACS catalysis, 2025)
The synthesis of active pharmaceutical ingredients (APIs) containing heteroaromatic motifs often relies on palladium-catalyzed Suzuki-Miyaura coupling (Pd-SMC), a transformation that can account for a significant portion of the production costs for small-molecule drugs. Nickel-catalyzed SMC offers a more compelling alternative; however, its large-scale implementation has been hindered by high catalyst loadings and a limited scope of heterocyclic coupling partners. Another unmet need in process synthesis is the adoption of polar solvents, such as alcohols and water, to reduce waste generation, improve safety, and improve compatibility with hydrophilic molecules. Here, we introduce a ( -ProPhos)Ni catalyst that enables efficient and robust Ni-SMC of heterocycles in -PrOH and water. The -ProPhos ligand features a phosphine moiety tethered to three hydroxyl groups, which can substitute the halide in the oxidative addition intermediate to form a nickel-alkoxy species. This pathway not only facilitates transmetalation but also enhances catalyst stability. Moreover, the hydrophilic nature of the ligand allows Ni-SMC to be performed in pure water. The ( -ProPhos)Ni catalyst accommodates a wide range of heteroaromatic core structures, including those present in APIs, with catalyst loadings as low as 0.03-0.1 mol %. The method has been validated on decagram scale and represents a versatile platform with significant potential for adoption in commercial process synthesis.